KAJIAN RISIKO BANJIR SUNGAI KAMPAR TERHADAP LINGKUNGAN DAN SOSIAL - EKONOMI MASYARAKAT DI KECAMATAN KAMPAR KABUPATEN KAMPAR PROVINSI RIAU - Muhammad Fikky Hidayat; Mubarak; Sigit Sutikno (EcoNews, 2020)
The impact of flooding will increase with the occurrence of climate change and population growth in an area, one of which is on the banks of the Kampar River, Kampar District, Kampar Regency. Then needed efforts to prevent flooding and overcome it. One of them is by analyzing flood risk using spatial data analysis with the help of ArcGIS technology and the application of HEC-RAS to provide an overview the level of flood danger, the level of vulnerability, the level of flood risk and preventive measures that can be done. The results showed that the area of flood inundation occurred in residential areas, rice fields, and plantation. Based on the results of the analysis of the hazard level in 5 times and the total level of vulnerability, obtained 5 levels of risk according to the time period, namely, a very low risk level of 91.7%, low 4.9%, moderate 0.3%, high 0.4%, and very high 2.8% of total area of research. The level of risk is very high spread evenly around the riverbanks of Kampar District. one of the structural efforts in reducing the risk of flooding in Kampar Subdistrict are the making of dyke such as in Pulau Sarak and Rumbio Villages, provision of permanent shelter, and periodic physical maintenance of hydropower reservoirs in the dry season. Furthermore, non-structural efforts such as making evacuation route maps, changing land use patterns, procurement of Kotopanjang water level information boards, and the importance of enforcing regulations not to throw garbage into the river.